Tattoo Ink Metal Nanoparticles: Assessment of Toxicity In Vitro and with a Novel Human Ex Vivo Model - Beatrice Battistini; Daniela Lulli; Beatrice Bocca; Maria Luigia Carbone; Carmela Ramondino; Stefano Caimi; Alessio Capone; Ezio Maria Nicodemi; Elena Dellambra; Isabella De Angelis; Cristina Maria Failla (Nanomaterials)
Tattoo inks contain varying amounts of metal nanoparticles (NPs) < 100 nm that, due to their unique physicochemical properties, may have specific biological uptake and cause skin or systemic toxicities. The toxic effects of certified reference standards of metal NPs and samples of commercially available tattoo inks were investigated using an in vitro system and a novel human ex vivo model. In vitro toxicity was evaluated using vitality assays on human skin cells (HaCaT cell line, primary fibroblasts, and keratinocytes). No toxicity was observed for Al2O3, Cr2O3, Fe2O3, and TiO2 NPs, whereas CuO NPs showed dose-dependent toxicity on HaCaT and primary fibroblasts. Fibroblasts and keratinocytes were also sensitive to high concentrations of ZnO NPs. Reference standards and ink samples were then injected ex vivo into human skin explants using tattoo needles. Histological analysis showed pigment distribution deep in the dermis and close to dermal vessels, suggesting possible systemic diffusion. The presence of an inflammatory infiltrate was also observed. Immunohistochemical analysis showed increased apoptosis and expression of the inflammatory cytokine interleukin-8 in explants specifically tattooed with the reference standard or red ink. Taken together, the results suggest that the tattooing technique leads to exposure to toxic metal NPs and skin damage.